Re‐examining TG‐142 recommendations in light of modern techniques for linear accelerator based radiosurgery. Issue 10 (13th September 2016) - Faught, Austin M.; Trager, Michael; Yin, Fang‐Fang; Kirkpatrick, John; Adamson, Justus
Abstract : Purpose: The recent development of multifocal stereotactic radiosurgery (SRS) using a single isocenter volumetric modulated arc theory (VMAT) technique warrants a re‐examination of the quality assurance (QA) tolerances for routine mechanical QA recommended by the American Association of Physicists in Medicine Task Group Report Number 142. Multifocal SRS can result in targets with small volumes being at a large off‐axis distance from the treatment isocenter. Consequently, angular errors in the collimator, patient support assembly (PSA), or gantry could have an increased impact on target coverage. Methods: The authors performed a retrospective analysis of dose deviations caused by systematic errors in PSA, collimator, and gantry angle at the tolerance level for routine linear accelerator QA as recommended by TG‐142. Dosimetric deviations from multifocal SRS plans ( N = 10) were compared to traditional single target SRS using dynamic conformal arcs ( N = 10). The chief dosimetric quantities used in determining clinical impact were V 100% and D 99% of the individual planning target volumes and V 12Gy of the healthy brain. Results: Induced errors at tolerance levels showed the greatest change in multifocal SRS target coverage for collimator rotations (±1.0°) with the average changes to V 100% and D 99% being 5% and 6%, respectively, with maximum changes of 33% and 20%. A reduction in the induced error to half the TG‐142 tolerance (±0.5°) demonstrated similar changes in coverage loss to traditional single target SRS assessed at the recommended tolerance level. The observed change in coverage for multifocal SRS was reduced for gantry errors (±1.0°) at 2% and 4.5% for V 100% and D 99%, respectively, with maximum changes of 18% and 12%. Minimal change in coverage was noted for errors in PSA rotation. Conclusions: This study indicates that institutions utilizing a single isocenter VMAT technique for multifocal disease should pay careful attention to the angular mechanical tolerances in designing a robust and complete QA program.